A chatbot service for use in video game development - Larsen, Alec John (My University, 2015)
Character dialogue writing for modern digital games is a di cult process as many of them are non-linear and as such the authors have to write many di erent versions of the characters' dialogues to compensate for di erent orders that the players may perform the tasks. The proposed solution is to replace game cut-scenes with interactive dialogue using a chatbot - a computer program that simulates conversation by responding to user's text inputs in a natural language such as English. This falls into the eld of interactive ction. By investigating existing interaction ction systems it was determined that they are di cult to author, use prede ned dialogue and do not handle mood. The proposed solution allows authors to create di erent non- playable characters (NPCs) using a single chatbot, based on the Arti cial Linguistic Internet Computer Entity (A.L.I.C.E.) open source project. This single chatbot acts as the knowledge-base for all the non-playable characters (NPCs) and provides stock responses to the player's inputs. These stock responses are then translated to match the NPC being interacted with. The translation takes the NPCs' dialects and moods into account, generating emergent dialogue. This approach simpli es the authoring approach as the knowledge-base is created once, independently of the NPCs and simple rules are de ned that allow each NPC to convey the relevent persona. The general chatbot and NPC translation rules are created using a GUI. The hedonic quality of the GUI was tested by ve people via a questionnaire. This showed that while the GUI is easy to use, the general chatbot work ow could be simpli ed. A test game was created and 35 people rated the system via a questionnaire. This gave a pleasing qualitative result as the NPCs are e ective at conveying information, their responses are variable, their personas are evident through their responses and players noticed a change in mood. Theoretical analysis shows that the simple rules can produce extremely variable outputs.